Pelatihan Penyusunan Laporan Keuangan Berbasis Excel untuk UMKM - Agus Fuadi; Vista Yulianti; Fany Apriliani (Jurnal Pengabdian Masyarakat, 2026)
This community service activity was conducted to address the limited financial management capacity of Micro, Small, and Medium Enterprises (MSMEs) in Kabupaten Bekasi, particularly in preparing systematic and reliable financial statements. The program aimed to improve MSMEs’ financial literacy and practical skills through Excel-based financial statement training. The activity employed a participatory training method combining socialization, hands-on practice, and mentoring, involving 15 MSME participants. The training was conducted at Universitas Pelita Bangsa and facilitated by a team consisting of lecturers and a student. The findings indicate a significant improvement in participants’ ability to record daily transactions digitally, prepare simple income statements and balance sheets, and understand the importance of separating personal and business finances. Beyond technical skills, the program fostered increased awareness, confidence, and the emergence of local peer support among participants. The activity implies that Excel-based financial training is an effective, low-cost, and scalable approach to strengthening MSME financial governance and supporting business sustainability.